Deployable Explainability for NLP Use Cases in E-commerce - Avinash, Vasarla (Global journal of Business and Integral Security, 2023)
This dissertation examines deployable explainability for NLP use cases in e-commerce using Amazon Musical Instrument Reviews. As NLP models are utilised for sentiment analysis, product recommendation, chatbots, and e-commerce text classification, transparency and interpretability are becoming more crucial. We examine the pros and cons of explainability techniques in NLP models for e-commerce applications using Amazon Musical Instrument Reviews. The literature review explains why natural language processing requires explainability and evaluates existing techniques. The Amazon Musical Instrument Reviews use case illustrates how explainable NLP may affect online company processes. Additionally, a methodical plan for integrating explainability approaches into NLP models for e-commerce is provided. Collecting data, training a model, including an explainability technique, and evaluating performance are all part of this process. The benefits of deployable explainability are demonstrated using an Amazon Music Instrument Reviews analysis. The investigation includes such elements as data gathering, models for natural language processing, and explainability strategies. The evaluation of performance considers the model's precision and the clarity of the system's explanation. The thesis addresses interpretability-performance trade-off, scalability, user acceptability, and ethical problems related to explainability in NLP models. These issues are addressed by simplifying and standardizing explainability approaches, boosting scalability and efficiency, resolving user acceptance and trust concerns, and ensuring ethical use of explainable NLP models. This thesis sheds light on the challenges and opportunities of incorporating transparency and interpretability into NLP systems, contributing to deployable explainability in ecommerce NLP use cases. This study uses Amazon Musical Instrument Reviews to demonstrate how explainable NLP models may improve user confidence, decision-making, and regulatory compliance in e-commerce platforms. Finally, the thesis emphasises the necessity to create and apply deployable explainability methodologies to a wide range of e-commerce use cases outside Amazon Musical Instrument Reviews.